Paul R. Brass. Ethnicity and Nationalism: Theory and Comparison. New Delhi: Sage Publications. 1991. x+358 pages. Hardbound. Indian Rupees 325.00 (The Pakistan Development Review, 1996)
This book is a collection of nine essays. Except for the last chapter, all the essays were written between 1978 and 1990 and are extentions of an earlier work, Language, Religion, and Politics in North India (Cambridge University Press) published by the author in 1974. Two main arguments constitute the theme of the book. First, that ethnicity and nationalism are social and political constructions of modern conditions rather than reflections of primordial identities. Second, that both these constructions are related to the role of a centralising state. They depend upon the kinds of alliances that are made between the state and the regional or other non-dominant élites. As such, ethnicity and nationalism are seen as the outcome of interactions between the state leadership and the élites from non-dominant ethnic groups, especially the groups on the peripheries of such states.